Evaluation of calibration factor of OSLD toward eye lens exposure dose measurement of medical staff during IVR. Issue 11 (14th October 2020) - Asahara, Takashi; Hayashi, Hiroaki; Goto, Sota; Kimoto, Natsumi; Takegami, Kazuki; Maeda, Tatsuya; Kanazawa, Yuki; Okazaki, Tohru; Hashizume, Takuya
Abstract: The eye lens is a sensitive organ of which an x‐ray exposure dose should be managed during interventional radiology (IVR). In the actual situations, the eye lens is exposed to scattered x‐rays; they have different from the standard x‐ray energies which are used for general dose calibration of the dosimeter. To perform precise dose measurement, the energy dependence of the dosimeter should be properly accounted for when calibrating the dosimeter. The vendor supplies a calibration factor using 80‐kV diagnostic x‐rays under a free‐air condition. However, whether it is possible to use this calibration factor to evaluate the air kerma during the evaluation of the eye lens dose is unclear. In this paper, we aim to precisely determine calibration factors, and also examine the possible application of using a vendor‐supplied calibration factor. First, the x‐ray spectrum at the eye lens position during fluoroscopy was measured with a CdTe x‐ray spectrometer. We mimicked transfemoral cardiac catheterization using a human‐type phantom. Second, we evaluated the doses and calibration factors at three dosimetric points: front and back of protective goggles, and the front of the head (eye lens position). We used the measured x‐ray spectrum to determine the incident photon distribution in the eye lens regions, and x‐ray spectra corresponding to the dosimetric points around the eye lens were estimated using Monte Carlo simulation. Although the calibration factors varied with dosimetric positions, we found that the factors obtained were similar to the vendor‐supplied calibration factor. Furthermore, based on the experiment, we propose a practical way to calibrate an OSL dosimeter in an actual clinical situation. A person evaluating doses can use a vendor‐supplied calibration factor without any corrections for energy dependences, only when they add a systematic uncertainty of 5%. This evidence will strongly support actual exposure dose measurement during a clinical study.